Kondisi Tenaga Kerja pada Sektor Pertanian, Kehutanan dan Perikanan Tahun 2020 di Provinsi Jawa Tengah - Ahmad Zaenun Faiz (Jurnal Ketenagakerjaan, 2021)
Agriculture, forestry and fishing is the highest workforce in Central Java Province with 4,608,261 people work in it. Despite being the third highest GDRP in Central Java Province 2020, this sector is ranked bottom sixth on productivity per capita. This issue can be seen from several aspects of employment such as the age of the workforce, education level, and type and status of work. This study using qualitative descriptive method to explain the condition of agriculture, forestry and fishing labour in Central Java Province by analysing National Workforce Survey (Sakernas) for the period of August 2016-2020. The result show that several conditions such as ageing workforce, lower education labour and subsistence agriculture dominant-farming system conduce the productivity per capita is low.